1997
DOI: 10.1108/02635579710161296
|View full text |Cite
|
Sign up to set email alerts
|

The impact of information systems on the efficiency of banks: an empirical investigation

Abstract: Financial institutions, and banks, in particular, are one of the largest investors in information systems (IS) and information technologies (IT) and there are indications that this trend is likely to continue. However, there is growing concern that IS investments are not yielding the anticipated results, an issue that is of grave concern to many CEOs and top managers. One way to address this concern is to analyse the relationship, if any, between investments in IS and an organization’s efficiency measures. Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…It is therefore argued that the library MIS would provide the means and methods to manage multimedia-computer based information systems to help gain useful, and timely information through its objective of satisfying scholarly, academic, administrative and information needs of the University. Uma and Collins (1997) conducted an empirical study that evaluated the contribution of MIS to various productivity and efficiency measures in a bank. The survey was mailed to the CIOs of all member banks of the Florida Bankers Association and was found that banks rely heavily on mainframes, minicomputers, microcomputers, and workstations.…”
Section: Makingmentioning
confidence: 99%
“…It is therefore argued that the library MIS would provide the means and methods to manage multimedia-computer based information systems to help gain useful, and timely information through its objective of satisfying scholarly, academic, administrative and information needs of the University. Uma and Collins (1997) conducted an empirical study that evaluated the contribution of MIS to various productivity and efficiency measures in a bank. The survey was mailed to the CIOs of all member banks of the Florida Bankers Association and was found that banks rely heavily on mainframes, minicomputers, microcomputers, and workstations.…”
Section: Makingmentioning
confidence: 99%
“…They gave the 'dehumanization of banking' as the main reason for failure, coupled with inappropriate measures of technological investment, such as ROI (return on investment). Research has suggested that such short-term critera are inappropriate because the returns on relationships are long term and dif cult to quantify, though ultimately of more importance (Gupta and Colins, 1997). Therefore, whilst the banking community appears to be investing in technical infrastructures, the investment in tacit knowledge to provide the interface with the client of the relationship is neglected.…”
Section: Empirical Workmentioning
confidence: 99%
“…According to Gupta and Collins (1997), most of the successful financial institutions have clearly demonstrated that information systems and technologies can be a powerful competitive weapon that can be used to capture market share, improve customer service, reduce operating costs, and also create new products and services [Lederer et al, 1988;Gupta el al., 1997]. Yet measuring the return on investments in Information Systems is important and almost impossible.…”
Section: Information Systems and Efficiencymentioning
confidence: 99%
“…This is mainly since the benefits obtained from Information Systems are intangible and long term. According to Gupta (1997) the survey was conducted by mailing member banks of FBA5. Multi-part questions were broadly divided into the following categories or factors identified.…”
Section: Information Systems and Efficiencymentioning
confidence: 99%
See 1 more Smart Citation